Proceedings. 14th International Conference on Computer Communications and Networks, 2005. ICCCN 2005.
DOI: 10.1109/icccn.2005.1523837
|View full text |Cite
|
Sign up to set email alerts
|

Scalable IP-VPN flow control mechanism supporting arbitrary fairness criteria - part 1: architecture design

Abstract: In recent years, IP-based virtual private networks (IP-VPNs), which provide a virtual privately owned network over an IP network, have attracted attention. With existing IP-VPNs, however, there is a serious problem that fairness among IP-VPN customers is not satisfied. In this paper, we first discuss design objectives of a control mechanism for achieving fair IP-VPN services: achieving inter-VPN fairness, achieving intra-VPN fairness, easy deployment into existing IP networks, and achieving a high scalability.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(5 citation statements)
references
References 19 publications
0
5
0
Order By: Relevance
“…This paper quantitatively evaluates the effectiveness of I2VFC proposed in our previous work [4] through simulation experiments and prototype system experiments. The results demonstrated that (1) inter-VPN fairness can be achieved with an extremely high accuracy regardless of settings of I2VFC control parameters, (2) arbitrary fairness including the MaxMin fairness can be achieved even in a network with multiple bottleneck links, (3) congestion of the bottleneck link is dispersed, and consequently fairness among TCP connections (intra-VPN fairness) is improved, and (4) our I2VFC has a practically sufficient scalability in terms of the transfer rate and the number of VPNs accommodated.…”
Section: Discussionmentioning
confidence: 98%
See 4 more Smart Citations
“…This paper quantitatively evaluates the effectiveness of I2VFC proposed in our previous work [4] through simulation experiments and prototype system experiments. The results demonstrated that (1) inter-VPN fairness can be achieved with an extremely high accuracy regardless of settings of I2VFC control parameters, (2) arbitrary fairness including the MaxMin fairness can be achieved even in a network with multiple bottleneck links, (3) congestion of the bottleneck link is dispersed, and consequently fairness among TCP connections (intra-VPN fairness) is improved, and (4) our I2VFC has a practically sufficient scalability in terms of the transfer rate and the number of VPNs accommodated.…”
Section: Discussionmentioning
confidence: 98%
“…TCP's congestion avoidance phase operating on end hosts corresponds to AIMD window flow control with a = 1.0 and b = 0.5. Hence, it is expected that I2VFC's window flow control operates satisfactorily with parameter settings of a < 1.0 and b < 0.5 [4].…”
Section: A Case Of a Single Bottleneck Linkmentioning
confidence: 98%
See 3 more Smart Citations